Performance of Indonesia's Sharia Capital Market for the 2022 Period - Atika Zahra Maulida; Risda Risdiana; Agus Purnomo (Universitas Darussalam Gontor, 2023)
Islamic capital markets instruments such as stocks, mutual funds, and sukuk are tools to drive economic growth through the capital market sector. The financial sector's performance in the first semester remained stable in 2022. The indicator that is getting stronger in the JCI index is 5.02% or a year-to-date level of 69 11.58 as of June 2022. This article aims to find out the performance of the Indonesian Islamic capital market for the 2022 period. This research uses a qualitative method with a literature review approach regarding the development and growth of sharia capital market performance after Covid-19 pandemic. The result of the discussion for the population has an Islamic majority population, so the capital market industry is expected. To accommodate and collect contributions from Muslim citizens to be active in the stock market, especially the Islamic stock market, and a local investor in the Indonesian Sharia capital market. Realize naturally that investment products are developed following Islamic principles and teachings. The financial sector's performance in the first semester remained stable in 2022. The indicator getting more assertive in the JCI index is 5.02% or a year-to-date level of 69 11.58 at the end of June 2022.